4p2+8p=0

Factor 4p out of 4p2.

4p(p)+8p=0

Factor 4p out of 8p.

4p(p)+4p(2)=0

Factor 4p out of 4p(p)+4p(2).

4p(p+2)=0

4p(p+2)=0

Divide each term in 4p(p+2)=0 by 4.

4p(p+2)4=04

Simplify 4p(p+2)4.

Cancel the common factor of 4.

Cancel the common factor.

4p(p+2)4=04

Divide p(p+2) by 1.

p(p+2)=04

p(p+2)=04

Apply the distributive property.

p⋅p+p⋅2=04

Simplify the expression.

Multiply p by p.

p2+p⋅2=04

Move 2 to the left of p.

p2+2p=04

p2+2p=04

p2+2p=04

Divide 0 by 4.

p2+2p=0

p2+2p=0

Factor p out of p2.

p⋅p+2p=0

Factor p out of 2p.

p⋅p+p⋅2=0

Factor p out of p⋅p+p⋅2.

p(p+2)=0

p(p+2)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

p=0

p+2=0

Set the first factor equal to 0.

p=0

Set the next factor equal to 0.

p+2=0

Subtract 2 from both sides of the equation.

p=-2

p=-2

The final solution is all the values that make p(p+2)=0 true.

p=0,-2

Solve for p 4p^2+8p=0